The influence mechanism of effective stress, adsorption effect and Klinkenberg effect on coal seam permeability - Wang, Mian; Yang, Yongliang; Zhou, Yinbo; Shi, Hanfeng; Huang, Jilei (Frontiers in Energy Research, 2023)
Permeability is an important parameter in the process of coalbed methane exploitation. To improve the production efficiency of coalbed methane and explore the control mechanism of the gas flow law in coal, the permeability of helium and nitrogen in the same coal sample was tested under different effective stress (the difference between external stress and pore pressure of coal mass) and pressure by using the seepage device. Based on the gas flow theory, the interaction mechanism of effective stress, adsorption effect and Klinkenberg effect in controlling the permeability has been analyzed. Increasing the gas pressure will enhance the adsorption and deformation ability of coal, causing the reduction of pore size, while it will also cause the reduction of effective stress and stress deformation. There is a certain competition between them under the same external stress condition, which will lead to the change of pore and then affect the permeability of coal seam. The Klinkenberg effect will lead to more complex change factors of permeability, especially in laboratory experiments. Both adsorption deformation and stress deformation will affect the pore structure of coal body, which will also lead to changes in the influence degree of Klinkenberg effect on apparent permeability. Under the influence of adsorption effect, the Klinkenberg effect may be a variable. The experimental results in this work elaborate the microscopic control mechanism of gas permeability change in coal. It can not only provide important guidance for gas injection technology, but also enrich the theory of coal seam gas flow.